DNA repair and gene editing: the director's cut. (23rd December 2021) - Doughty, Kelly; Baldock, Robert A.
Abstract : Novelists and screenwriters have bombarded our imaginations with the idea of genetic engineering. From superhero origin stories to theme parks inhabited by dinosaurs, the prospect of re-writing the genetic code has inspired many and raised many ethical questions. The potential for these tools in medicine and biological sciences to prevent genetic diseases is readily being explored. Recent successes include destruction of simian immunodeficiency virus DNA from infected rhesus macaque monkeys (synonymous to the human immunodeficiency virus). The diverse power of these tools is also helping to control mosquito populations and supress the spread of malaria. New gene-editing tools have made genome editing faster, more accurate and cheaper than ever before, but how do they work? And how do we know whether the desired edits will be made?